STUDI FENOMENOLOGI TENTANG GAMBARAN PSYCHOLOGICAL WELL-BEING PADA PEDAGANG DI PASAR LEGI PASCA PERISTIWA KEBAKARAN - Setyawan, Endika Rachel; Priyatama, Aditya Nanda (Program Studi S1 Psikologi, 2024)
The fire that occurred at Legi Market, Surakarta caused many losses suffered by almost all merchants in the market. The impact of the losses suffered is not only on the goods or the stalls burned, but also has an impact on the psychological state of the merchants. This research is a qualitative research using the method of phenomenological study. The purpose of this study was to describe the psychological well-being of Legi market merchants after the fire. Respondents or participants in this study were four individuals who met the criteria of being Legi Market merchants, affected by the Legi Market fire incident and had a non-coercive will by completing an informed consent to participate in the research, as well as four other important ones. The sampling technique used was purposive sampling. The data collection methods used were blank curriculum vitae, observation and interviews. The data analysis used in this study is the technique of Interpretative Phenomenological Analysis (IPA). The results of the survey conducted among Legi Market merchants who were affected by the fire showed that all four respondents had good psychological well-being. All respondents complete aspects of psychological well-being. All respondents were able to come to terms with their situation after the fire incident and began to rise to achieve good psychological well-being in various ways. Keywords: psychological well-being; merchants; fire